Strategi Kebudayaan Perjuangan Pahlawan Nasional Pangeran Sambernyowo - Eko Punto Hendro (Endogami: Jurnal Ilmiah Kajian Antropologi, 2017)
The beginning of the struggle of Prince Sambernyowo begins when his father was exiled to Sri Lanka, the first struggle was done by helping Mas Garendi invade Kartosuro Palace, because Pakubuwono I in cooperation with the VOC. Thap next Prince Sambernyowo held a direct resistance to the VOC which was marked by wars in various fields, among others, in Kartosuro, in Ponorogo, in Sitakepyak Rembang, in Vredeburg Fortress Yogyakarta, and others which then ended with emerging Salatiga Agreements. Many heritages Pangeran Sambernyowo during his struggle to ascend the throne at Pura Mangkunegaran, in addition to the palace Pura Mangkunegaran, among others Astana Mangadeg in Karanganyar, Inscription Nglaroh and Tugu Pusaka in Nglaroh Wonogiri, Pablengan Karanganyar and Sendang Siwani Wonogiri. Indeed Prince Sambernyowo is not a freedom fighter of the Republic of Indonesia, but he once laid the foundation stone to stand upright this republic